Clinical Importance of MRI Lumbar Spine in Lower Backache - Nazia Azeem, Muhammad Anwar, Malik Osama Tanweer (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To examine the effectiveness and clinical significance of lumbar spine MRI in chronic lower-back ache patients and its relevant radiculopathies. Study design: Cross-sectional descriptive study Place and duration of dtudy: Department of Radiology, Sir Syed College of Medical Sciences for Girls Karachi from 1stJune 2020 to 30thNovember 2020. Methodology: Ninety patients of both males and females, between the ages of 20-75 years with a history of bilateral or unilateral lower limbs radiculopathy, lower back numbness and pain were included. The patients with a history of vascular malformation, metastasis, tumour, infection, and trauma were excluded. Lumbar spine MRI was performed by MRI scanner. At the following levels, the scan was taken: L5-S1, L4-L5, L3-L4, L2- L3. Results: The mean age was 44.64±15.67 years. Eighty percent of patients showed osteophytes formation and disc desiccation signs, 53.5% of patients showed signs of numbness, and 36.7% of patients has bilateral lower-limbs radiculopathies complaints, whereas 91.1% had shown signs of diffuse disc bulge on spinal level of L5-S1. In 100 percent of patients, neural foramina were compromised at level L4-L5 to which in 98.9% of patients there was a “nerve root compression” at this level. Mostly it has been seen that level L2-L3 is spared. At level, L2-L3 hundred percent of patients did not reveal any important ligamentumflavum hypertrophy and 98.9 percent of people have no “facet joint hypertrophy”. Conclusion: The lower back pain frequency is higher in males as well as in females. In a patient who has lower back pain, the Disc desiccation was frequent. Because of spinal canal stenosis, foraminal canal and nerve root compressions the most general targeted sites were L5-S1 and L4-L5. Keywords: Lumbar spine, Magnetic resonance imaging, Lower backache